The Impact of Non-Tariff Measures on Indonesian Seaweed Exports to the International Market - Rini Dwi Lestari; Harianto Harianto; Amzul Rifin (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
With the increasing global demand for seaweed and Indonesia’s position as one of the world’s largest producers, understanding the barriers to export growth has become increasingly urgent. This study investigates the impact of Non-Tariff Measures (NTMs) on Indonesia’s seaweed exports to six major destination countries—Chile, China, Denmark, Japan, Spain, and the United States—over the period 2012 to 2022, using annual panel data. A panel data regression analysis with the Random Effect Model (REM) is employed to examine the influence of various factors, including import prices, population, GDP per capita of the importing countries, and NTMs in the form of Sanitary and Phytosanitary (SPS) standards and Technical Barriers to Trade (TBT). The findings show that import prices, GDP per capita, and the implementation of SPS and TBT measures negatively affect Indonesia’s seaweed export volume, while population growth in the importing countries has a positive and significant impact. Key challenges hindering Indonesia’s seaweed exports include stringent SPS requirements, food safety regulations, and product rejections due to contamination and non-compliance with international standards. To improve the competitiveness of Indonesian seaweed in the global market, it is essential to strengthen product quality, comply with international regulations, promote technological inovation, and provide targeted support for exporters.